The influence of Russian traditions on the formation of Khakass farm housing in Khakass-Minusinsk region in 19th - 20th centuries - Valentina N. Tuguzhekova; Evgeny V. Prischepa (Novye Issledovaniâ Tuvy, 2019)
The article deals with the problems of the development of farm housing among the indigenous inhabitants of Khakass-Minusinsk region in the 19th and 20th centuries. As a result of the development and settlement of the region, the cultural and economic relationships of the Khakass people with the Russians meant establishing contacts between different cultural traditions. This triggered the process of cultural interaction, an important place wherein belonged to the development and evolution of the main types of farm housing.